Penyelesaian Konflik Tanah Warisan Pada Keluarga Batak Toba “Sapopparan” Di Kecamatan Pakkat - Ranti Miranda Uliarta Manalu; Marisa Elsera; Siti Arieta (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
The patrilineal kinship system of the Toba Batak community, the positions of boys and girls have different responsibilities and positions. Likewise in terms of the distribution of inherited land, the position of women is very weak. This is what ultimately causes conflict. This study aims to find out and understand the resolution of inherited land conflicts in members of the sapopparan family in Pakkat District. This study used qualitative research methods. This study uses the theory of conflict by George Simmel which focuses on the forms of conflict and conflict resolution that occur in every family involved in a family inheritance land conflict. Based on the findings, the researchers found that there were four cases of family inheritance land conflicts in Karya Village, Pakkat District. The findings of this study illustrate that family members who are in conflict are involved in personal conflicts. In the conclusion of the results of this study, there are two conflict resolutions that occur in every family involved in the conflict. The settlement that is pursued by each family is through conflict resolution and conflict reconciliation.